First Report of Angiopsora paspalicola Causing Leaf Rust on Paspalum conjugatum in Malaysia - Khoo, Ying Wei; Gao, Ling; Khaw, Yam Sim; Tan, Hui Teng; Li, Shifang; Chong, Khim Phin (Plant disease, 2023)
(family Poaceae), locally known as Buffalo grass, is a perennial weed that can be found in rice field, residential lawn, and sod farm in Malaysia (Uddin et al. 2010; Hakim et al. 2013). In September 2022, Buffalo grass with rust symptoms and signs were collected from the lawn located in Universiti Malaysia Sabah in the province of Sabah (6°01'55.6"N, 116°07'15.7"E). The incidence was 90%. Yellow uredinia were observed primarily on the abaxial surface of the leaves. As the disease progressed, leaves were covered with coalescing pustules. Microscopic examination of pustules revealed the presence of urediniospores. Urediniospores were ellipsoid to obovoid in shape, contents in yellow, 16.4-28.8 x 14.0-22.4 μm and echinulate, with a prominent tonsure on most of the spores. A fine brush was used to collect yellow urediniospores, and genomic DNA was extracted based on Khoo et al. (2022a). The primers Rust28SF/LR5 (Vilgalys and Hester 1990; Aime et al. 2018) and CO3_F1/CO3_R1 (Vialle et al. 2009) were used to amplify partial 28S ribosomal RNA (28S) and cytochrome c oxidase III (COX3) gene fragments following the protocols of Khoo et al. (2022b). The sequences were deposited in GenBank under accession numbers OQ186624- OQ186626 (985/985 bp) (28S) and OQ200381-OQ200383 (556/556 bp) (COX3). They were 100% similar to 28S (MW049243) and COX3 (MW036496) sequences. Phylogenetic analysis using maximum likelihood based on the combined 28S and COX3 sequences indicated that the isolate formed a supported clade to . Koch's postulates were performed with spray inoculations of urediniospores suspended in water (10 spores/ml) on leaves of three healthy Buffalo grass leaves, while water was sprayed on three additional Buffalo grass leaves which served as control. The inoculated Buffalo grass were placed in the greenhouse. Symptoms and signs similar to those of the field collection occurred after 12 days post inoculation. No symptoms occurred on controls. To our knowledge, this is the first report of causing leaf rust on in Malaysia. Our findings expand the geographic range of in Malaysia. Albeit is a host of the pathogen, but the host range of the pathogen especially in Poaceae economic crops need to be studied. Weed management could be an effective way to eliminate inoculum sources of .